Pet and owner personality and mental wellbeing associate with attachment to cats and dogs - Ståhl Aada; Salonen Milla; Hakanen Emma; Mikkola Salla; Sulkama Sini; Lahti Jari; Lohi Hannes (Elsevier Inc., 2025)
Human-pet attachment can impact the life of both parties, and the identification of underlying characteristics related to attachment style can improve human-pet relationships. We employed <a href="https://www.sciencedirect.com/topics/biochemistry-genetics-and-molecular-biology/structural-equation-modeling" title="Learn more about structural equation modeling from ScienceDirect's AI-generated Topic Pages">structural equation modeling (SEM) to explore associations between human, dog, and cat personalities, owner mental well-being, unwanted pet behavior, and attachment styles in a sample of 2,724 Finnish pet owners (92% women) and their 2,545 dogs and 788 cats. Our findings reveal that owner neuroticism and poor mental well-being are linked to anxious pet attachment in both dog and cat owners. Pet characteristics, such as unwanted behavior and lower human sociability are associated with avoidant attachment style. Overall, this study highlights the significance of individual traits in both pets and owners contributing to insecure attachment styles and underscores the potential to enhance the well-being of both pets and their owners through a deeper understanding of these traits.